PENURUNAN GARAM KLORIDA AIR LAUT DENGAN MEMANFAATKAN MODIFIKASI PATI DARI LIMBAH BONGGOL PISANG AMBON (Musa paradisiaca var sapientum) - Aulia Husna Rabbani; Alimuddin -; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2015)
The research of desalination the sea water by utilization of the strach bump a “Pisang Ambon (Musa paradisiaca var sapientum)” modification has been done. Modification of starch bump “Pisang Ambon (Musa paradisiaca var sapientum)” had be a ability better than starch bump “Pisang Ambon (Musa paradisiaca var sapientum)” in the levels of chloride. The variation upon which to do to absorb chloride of sea water which are starch, starch been activated NaOH and starch acetate bump of a “Pisang Ambon (Musa paradisiaca var sapientum)”. Where The characteristic of the third ingredients were done by analysis FT-IR that showed the spectrum in the wavenumber of each of which are read the force –OH,C-H streaching, C-H bending, CO ester in the spectrum of starch and starch been activated with NaOH and then are read the ester C=O in the wave number of 1751,36/cm and C-O ester and forth on the wave number of 1234,44/cm to the full spectrum of starch acetate. The rendemen a modification of the starch was also shown the modified starch in the bump a “Pisang Ambon (Musa paradisiaca var sapientum)” then more starch obtained. And which after passed a sample of starch bumb “Pisang Ambon (Musa paradisiaca var sapientum)” wet sea water left in levels chloride 20.160,77 mg/L, in the starch bump “Pisang Ambon (Musa paradisiaca var sapientum)” dry sea water left in levels of chloride 19.783,23 mg/L, in the starch bump “Pisang Ambon (Musa paradisiaca var sapientum)” have been activated with NaOH wet sea water left in the levels of chloride 19.405,68 mg/L, in the starch bump “Pisang Ambon (Musa paradisiaca var sapientum)” have been activated with NaOH dry sea water left in levels of chloride 19.028,14 mg/L and in the starch acetat bump “Pisang Ambon (Musa paradisiaca var sapientum)” sea water left in levels of chloride 18.461,83 mg/L.Keywords: the water of the sea, salt chloride, spectrum FTIR, starch and modification of starch bump a Pisang Ambon (Musa paradisiaca var sapientum)